Dispersion-controlled docking preference: multi-spectroscopic study on complexes of dibenzofuran with alcohols and water. Issue 29 (15th July 2019) - Bernhard, D.; Fatima, M.; Poblotzki, A.; Steber, A. L.; Pérez, C.; Suhm, M. A.; Schnell, M.; Gerhards, M.
Abstract : The planarity and rigidity of dibenzofuran inverts the docking preference for increasingly bulky R-OH solvent molecules, compared to the closely related diphenyl ether. Now, London dispersion favors OH⋯π hydrogen bonding. Abstract : The structural preferences within a series of dibenzofuran–solvent complexes have been investigated by electronic, vibrational, and rotational spectroscopic methods probing supersonic jet expansions. The experimental study is accompanied by a detailed theoretical analysis including dispersion-corrected density functional theory, symmetry adapted perturbation theory, as well as coupled cluster approaches. The complementary, multi-spectroscopic results reveal a preferred OH⋯O structure for the smallest complex of dibenzofuran–water, whereas for the methanol complex an OH⋯π isomer is simultaneously observed. For the largest complex, dibenzofuran– tert -butyl alcohol, only a π-bound structure is found. These comprehensive investigations show that a completely inverse trend regarding the docking preference is observed by comparing the present results with the ones for analogous diphenyl ether complexes. This can be rationalized on the basis of the planarity/non-planarity and rigidity/flexibility of the different systems, providing valuable insight into the interplay between different non-covalent interactions. This analysis is a further step towards a quantitative description of very delicate energetic balances with the overall goal of yielding reliable structural predictions for non-covalently bound systems.